Effect of Wheat Flour and Yellow Pumpkin Flour Ratios on The Physical, Chemical Properties, and Preference Level of Cookies - Salma, Nabila; Setiyoko, Agus; Sari, Yuli Perwita; Rahmadian, Yudi (Journal of Agri-Food Science and Technology, 2023)
Cookies are made from flour, eggs, vanilla, margarine, and baking powder ingredients. The weakness of standard cookies is their low antioxidant content. Therefore, innovation is needed to increase the antioxidant level of these cookies. This study contributes to determining the effect of adding yellow pumpkin flour on selected cookies' physical, preference level, chemistry properties, and antioxidant activity. The proportion of adding pumpkin flour consists of 0%, 10%, 20%, 30%, 40%, and 50%. The physical analysis included color, texture, expansion volume, and the level of preference, including flavor, color, taste, texture, and overall, which are used to select the most preferred cookies by panelists. The chemical analysis includes moisture, ash, protein, carbohydrate contents, and IC50 value for the most preferred cookies by panelists. The findings indicated that the selected formula by the panelist was cookies with 20% pumpkin flour substitution. The physical characteristics of cookies are a lightness color of 54.15, a texture of 1572.7 gF, and an expansion volume of 46.2%. The chemical elements are as follows: moisture content of 4.68%, ash content of 1.53%, protein content of 8.15%, fat content of 26.10%, carbohydrate content by the difference of 59.54%, and IC50 as much as 84.84 ppm, which means that the selected cookies have intense antioxidant activity. The experiment's contribution was that increasing antioxidant intake through dietary choices can positively impact overall health and potentially reduce the need for medicinal intervention.